Learners' Perception of English Language Learning in Universal Secondary Schools in Kisoro District. - Ndagijimana, Ngenda (Kabale University, 2023)
The study investigated learners' perception of English language learning in secondary schools in Kisoro Municipality. It was guided by objectives which were to establish learners' positive perception of English learning in USE schools in Kisoro District, to investigate the learners' negative perceptions of English learning in USE schools in Kisoro District and to establish ways to improve on English learning in USE schools in Kisoro District. The study dopted a cross sectional research design. The study used a sample size of 249 respondents. Both purposive and simple random sampling techniques were used in selecting respondents. Dara collection was done using questionnaires and interview guide. The study established that English was one of favourite subjects for learners and students liked mastering English because it would help them get a good job in the future. In addition, studying English helped students to improve their personality and communicate in English effectively as well as rnabling students use modern technology effectively. The study established that that English was a difficult subject and at times students dodged its lessons. From the findings, it was established that they had not got any great wish to learn more than the basics of English. The study also established that students who claimed they got nervous in English classes were just making excuses. The study established that some students didn't attend English classes because they have negative perception towards learning it. The study found out that learners should be motivated by creating good learning environment, providing enough English instructional materials and teaching resources, assessing of students using appropriate continuous assessment strategies and encouraging students to have positive perception on learning English would improve on English learning in secondary schools in Kisoro District. The study recommended that learners should be motivated by creating good learning environment. There should be provision of enough English instructional materials and teaching resources as this would create positive perception and enhance English learning. Since effective learning takes place through interactive communication between the more knowledgeable person and the learner, there must be a more empowering plan to ensure that teachers and learners have basic capacity to use English as the medium of instruction. keywords: Learners' Perception, English Language Learning, Universal Secondary Schools, Kisoro District.